1999
DOI: 10.1097/00000539-199909000-00039
|View full text |Cite
|
Sign up to set email alerts
|

Peribulbar Anesthesia with Either 0.75% Ropivacaine or a 2% Lidocaine and 0.5% Bupivacaine Mixture for Vitreoretinal Surgery: A Double-Blinded Study

Abstract: Quick onset of block with prolonged postoperative analgesia is an important goal in regional anesthesia for ophthalmic surgery. Evaluating clinical properties of 0.75% ropivacaine and a 1:1 mixture of 2% lidocaine and 0.5% bupivacaine for peribulbar anesthesia, we demonstrated that ropivacaine has an onset similar to that of the lidocaine-bupivacaine mixture and provides a better quality of postoperative analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 8 publications
1
16
0
1
Order By: Relevance
“…However, the complete block developed in these observations to the 30th minute. Related to previous eye surgeries, a report was published that the time for the development and blockade duration compared when retrobulbar block was performed with ropivacaine and using a mixture (1 : 1) of bupivacaine and lidocaine [4]. Chelly [5] wrote that, to achieve surgical anesthesia of the sciatic nerve, 15-20 min are required if ropivacaine 0.75% is used and 10-20 min if 0.75% ropivacaine is mixed with 1.5% lidocaine.…”
Section: Introductionmentioning
confidence: 99%
“…However, the complete block developed in these observations to the 30th minute. Related to previous eye surgeries, a report was published that the time for the development and blockade duration compared when retrobulbar block was performed with ropivacaine and using a mixture (1 : 1) of bupivacaine and lidocaine [4]. Chelly [5] wrote that, to achieve surgical anesthesia of the sciatic nerve, 15-20 min are required if ropivacaine 0.75% is used and 10-20 min if 0.75% ropivacaine is mixed with 1.5% lidocaine.…”
Section: Introductionmentioning
confidence: 99%
“…12 They concluded that 0.75% ropivacaine has an onset similar to that of the 2% lidocaine and 0.5% bupivacaine mixture and provides a better quality of postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…12 Pa ti ent sa tis fac ti on was re ported as 83% in li do ca i ne-bu pi va ca i ne tre a ted gro up and 97% in ro pi va ca i ne tre a ted gro up in a study which com pa red pe ri bul bar anest he si a with eit her 0.75% ro pi va ca i ne or 2% li do ca i ne-0.5% bu pi va cai ne mix tu re for vit re o re ti nal sur gery. 13 In anot her study, re se arc hers re por ted a trend to wards bet ter sa tis fac ti on in pa ti ents ad mi nis te red le vo bu pi va cai ne com pa red to ro pi va ca i ne at 24 ho urs fol lo wing ope ra ti on.…”
Section: Discussionunclassified